The recent outbreak of acute severe hepatitis in children of unknown origin - what is known so far - Lurz, Eberhard; Lenz, Dominic; Bufler, Philip; Fichtner, Alexander; Henning, Stephan; Jankofsky, Martin; Kathemann, Simone; Melter, Michael; Oh, Jun; Pfister, Eva Doreen; Sturm, Ekkehard; Knoppke, Birgit; et al. (Journal of hepatology, 2022)
Recent studies have reported that pediatric acute liver failure of unknown origin is immune-mediated, with CD8+ T cells playing a key role. Moreover, investigation of superantigen-mediated T-cell activation by the SARS-CoV-2 spike protein in pediatric severe acute hepatitis is needed in the context of the proposed mechanism of multisystem inflammatory syndrome in children (MIS-C). We investigated the immunological characteristics of a Japanese pediatric patient with severe acute hepatitis post SARS-CoV-2 infection. The patient demonstrated autoimmune hepatitis-like liver histology with CD8+ lymphocyte-predominant infiltration. There was Th1-type immune skewing, including remarkable peripheral CD8+ T-cell activation and a skewed T cell receptor repertoire. We also found elevated plasma levels of the anti-SARS-CoV-2 spike-specific IgG antibody, and the titer peaked after treatment, as seen with MIS-C. These findings support that immunological activation involving SARS-CoV-2 spike protein plays a crucial role in a pediatric patient with acute severe hepatitis post SARS-CoV-2 infection.